The beach‐spawning California grunion Leuresthes tenuis eats and digests conspecific eggs. Issue 2 (21st September 2018) - Santos, Allison J.; Frederick, Alyssa R.; Higgins, Benjamin A.; Carrillo, Andres; Carter, Ariel L.; Dickson, Kathryn A.; German, Donovan P.; Horn, Michael H.
Abstract : Apparent egg cannibalism was investigated in the beach‐spawning California grunion Leuresthes tenuis . Three hypotheses were tested to determine whether L. tenuis regularly consumes and efficiently digests conspecific eggs. First, examination of the gut contents of adults collected at four spawning sites over two seasons showed that the intestines of most fish from all the sites (57–87%, n ≥ 30, each site) contained L. tenuis eggs. The two other hypotheses focused on digestion of the eggs. First, the force required to crush cannibalized eggs was significantly less than that for uncannibalized eggs (fertilized or unfertilized), indicating that ingestion weakens the egg chorions. Second, conspecific eggs fed to fish held in the laboratory visibly degraded as they passed through the gut. The eggs lost c . half of their protein content and about two‐thirds of their lipid content as they passed from proximal to distal regions of the gut, indicating that digestion occurred. Digestive enzyme activities of the gut further confirmed that L. tenuis can break down the contents of ingested eggs. Trypsin activity decreased and aminopeptidase activity increased posteriorly along the gut, whereas amylase and lipase activities exhibited less clear patterns by gut region. As far as is known, this study is the first to show that L. tenuis is an egg cannibal.